Analysis of Hospital and INA-CBG’S Rates of JKN Outpatient in Genteng Regional Public Hospital in 2021 - Triyudawati, Wiwik; Kustriyani, Anung; Prasasti, Azmi (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2468, 2023)
The Government's effort improves the health status of the Indonesian people by establishing a Jaminan Kesehatan Nasional (JKN). JKN’s program was formed by Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS Kesehatan). Payment of health costs by BPJS uses the Indonesian-Case Based Group (INA-CBG's) especially for advanced health care services. INA-CBG's is payment to the main health center for a predetermined service package according to the disease diagnosis category. This makes hospitals strive to continue providing quality health services to JKN patients while still controlling costs. The aim of this research is analyze the difference between the outpatient BPJS patient rates and INA-CBG's rates at the Genteng Regional General Hospital in 2021. The research method is a retrospective observational study with simple random sampling. The total sample was 400 obtained during the period January to December 2021. The results of the research showed that the hospital rates was IDR 105,995,056 and the INA-CBG's rates was IDR 89,484,300. It was known that there were three largest cost components including drugs (drugs and chronic drugs) was IDR 51,878,574 (48.70%); patient care costs was IDR 33,980,600 (24.65%); and consultation fee was IDR. 10,400,000 (9.40%). The three largest components of hospital rates included minor chronic disease procedures and dialysis procedures. The conclusion was hospital rates are greater than INA-CBG's rates.